2005
DOI: 10.1002/ajpa.20292
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal manifestations of rickets in infants and young children in a historic population from England

Abstract: Gross and radiographic changes characteristic of inadequate bone mineralization due to rickets are described in 21 immature skeletons from a 19th century urban population from Birmingham, England. The aims of the study are as follows: to evaluate and if possible augment existing dry-bone criteria for the recognition of rickets in immature skeletal remains; to investigate the value of radiography for the paleopathological diagnosis of rickets; and to compare and contrast the expression of rickets in this group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 20 publications
3
128
0
Order By: Relevance
“…The unilateral nature of the new bone formed around the right elbow is less characteristic of scurvy, as is the extensive new bone formation and destruction on the mandible. The endocranial and ectocranial bone changes described above may be also related to vitamin D deficiency (rickets) along with the abnormal bowing of the femora (Pitt 1995:1894, Ortner and Mays 1998, Mays et al 2006. Working long hours indoors can predispose people to developing vitamin D deficiency due to the lack of ultraviolet light on their skins and subsequent lack of formation of the vitamin in the skin.…”
Section: Evidence Of Metabolic Bone Diseasementioning
confidence: 99%
“…The unilateral nature of the new bone formed around the right elbow is less characteristic of scurvy, as is the extensive new bone formation and destruction on the mandible. The endocranial and ectocranial bone changes described above may be also related to vitamin D deficiency (rickets) along with the abnormal bowing of the femora (Pitt 1995:1894, Ortner and Mays 1998, Mays et al 2006. Working long hours indoors can predispose people to developing vitamin D deficiency due to the lack of ultraviolet light on their skins and subsequent lack of formation of the vitamin in the skin.…”
Section: Evidence Of Metabolic Bone Diseasementioning
confidence: 99%
“…Skeletal changes include bending deformities [95,96], metaphyseal flaring, and porosity of cortical bone [11,95,97]. These changes can affect the cranial vault, long bones, pelvis, ribs, and vertebrae.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…There have been advances in the study of vitamin deficiencies in children, particularly scurvy (vitamin C deficiency) and rickets (vitamin D deficiency), and methods have been established that enable the reliable identification of both conditions in child skeletons (Mays, Brickley, and Ives 2006;Brickley and Ives 2008). Studies have demonstrated differences in the affected age profile and severity of rickets in children living in urban and rural environments (Mays, Brickley, and Ives 2006).…”
Section: The Palaeopathology Of Childhoodmentioning
confidence: 99%
“…Studies have demonstrated differences in the affected age profile and severity of rickets in children living in urban and rural environments (Mays, Brickley, and Ives 2006). The broader age profile and less severe lesions in urban populations have been interpreted as a direct indication of the constant smoggy environment, whereas the somewhat unexpected severe lesions restricted to infants in rural environments are thought to have been due to familial efforts to care for already sickly children by keeping them indoors (Mays, Brickley, and Ives 2006;Murphy 2015). Recent research based on clinical advances has proposed a new interpretative model for assessing the impact of vitamin D deficiency in past populations.…”
Section: The Palaeopathology Of Childhoodmentioning
confidence: 99%